Design and Usability Testing of a Web-Based Intervention Module for Obesity: CoPT Nutri Trail - Yaacob, Norhasniza; Ismail, Amirah; Mahmud, Mohd Izwan; Abd Talib, Ruzita (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Online interventions have emerged as innovative solutions to address health issues, notably obesity, while minimizing the necessity for in-person interactions during the recent COVID-19 pandemic. There is urgency in designing and developing an appropriate online intervention module within a web-based application. This study aims to describe the design process and usability of the online Canteen Operators, Parents, and Teachers (CoPT Nutri Trail) module for an upcoming school-based obesity intervention. MATERIALS AND METHODS: The design methodology consists of four phases: content development, design, web app development, and usability testing. The web application was designed to personalize usage for teachers, parents, and canteen operators to foster healthy environments for children. Thirteen experts, including teachers, nutritionists, and IT professionals, participated in the usability testing. RESULTS: All experts agreed that the design of the web application met the requirements of target users, requiring slight improvements in graphic design, language, and information elements. The web application tool was found acceptable, as the usability of alpha scores for all interface elements ranged from 68.2% to 86.6%, falling between good and very good scores. The content validation indices indicate good levels of validity (ranging from 0.83 to 1.00). CONCLUSION: The CoPT Nutri Trail web application is ready to be launched as a school-based intervention for obesity.